Advancing Responsible Sourcing in Mineral Value Chains (Springer Nature, 2024)
This book examines the responsible sourcing of raw materials within global value chains. With the need for a vast amount of additional raw materials to enable the global green energy transition, it examines the current responsible sourcing landscape, with the aim of bringing clarity and harmony to theories and practices that are characterized by systemic fragmentation. Normative elements are introduced to create a framework for a functioning responsible sourcing system built around the behavioural change of supply chain actors. Drawing from state of the art conceptual ideas and practical experience, an impactful and economically viable approach to the responsible sourcing of raw material is presented. This book sets out a vision of global value chains based on environmental, societal, and economic sustainability. It will be relevant to researchers, policymakers, and practitioners interested in resource economics and sustainable value chains. This is an open access book.